Model Transparansi Tata Kelola Sekolah Dasar Negeri (SDN) di Wilayah Jakarta Timur - Nurhattati Fuad; Fadhillah; Ahmad Jauhari HR (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
Abstract : The study aims to describe the practice/implementation of the transparency of the head of school in the school administration to analyse the needs of the information system of school administration as a basis for the elaboration of a transparency model of the SDN administration. Using the survey methodology with data collection techniques in the form of a lift filled by 248 school committee managers from 40 primary schools, enriched with focused discussions with 40 heads of schools and 40 teachers. The results of the questionnaire are presented and analyzed qualitatively. The results of the research show that the transparency of the government of the state primary school in East Jakarta City is in the category sufficient, but it is potentially to be developed through the information system of the school administration so that the hypothetical model of the transparent government system in SDN can be drawn. It is advised that DKI Jakarta should facilitate the acquisition of the system with its supporting devices, both IT advisor and operator resources. Schools should respond positively if transparency in school governance is implemented.